Factors Associated with Exclusive Breastfeeding 6 Months in Nonthaburi Province - ชัยโอภานนท์, สมพงษ์ (Journal of Preventive Medicine Association of Thailand, 2018)
The bureau of national statistics reported that Thai EBF rate was 12.3% in the year 2012, which was at a low rate. Maternal-child surveillance of Nonthaburi provincial health center reported that EBF rate of Nonthaburi were 54.50%, 60.85% in the year 2014 and 2015 respectively, which achieved the goal of 50% according to key performance index of Ministry of Public Health. The breastfeeding advocacy project in Nonthaburi should be credited as good practice one. This research aimed to study factors associated with Exclusive Breastfeeding 6 months (EBF) in Nonthaburi province. This research is a case-control study to compare factors of the group EBF more than 6 months with the group EBF less than 6 months for lesson learning to be applied in other arena of low EBF rate. The data was collected primarily from postpartum mothers through the questionnaires. Chi-squared test, Fisher’s exact test and Binary logistic regression were used to analyze the study data. The results showed that 243 postpartum enrolled the study. The group of EBF less than 6 months (Case group) was 122 participants, the group of EBF more than 6 months (Control group) was 121 participants, average age of both groups was 29.84 years. Analyzed data of factors associated with EBF 6 months showed that no experience in EBF one has less opportunity to achieve EBF 6 months than the experience one at 2.27 times (OR=2.27, 95%CI=1.23-4.18). Whose husband, father-mother, relatives and caregiver are main infant-rearing person has less success in 6 months EBF than maternal-own rearing at 5.23 times (OR=5.23, 95%CI=2.56-10.67). Whose of lower knowledge level about EBF has less opportunity to complete 6 months EBF than the higher one at 2.97 times (OR=2.97, 95%CI=1.42-6.16). Whose of middle attitude level has less opportunity to achieve EBF 6 months less than high attitude level one at 2.27 times (OR=2.27, 95%CI=1.09-4.70), Whose of low attitude level has opportunity to achieve EBF less than 6 months more than higher attitude level one at 4.18 times (OR=4.18, 95%CI=1.82-9.63). Conclusion: The study showed that personal factors associated with EBF were breastfeeding experience, maternal desire to EBF, higher graduation and better attitude. Social factors influence EBF were husband, relatives, infant caregiver. Government should state that Maternal milk is only one food for infants, and allowance post-partum leave for 3 months, also paternal leave 15 days in both governmental and private sectors. Included scaling up knowledge and attitude of EBF to mothers and main infant caregiver.